Antibacterial and Antifungal Activities of Leaf Extract of Morinda elliptica - HENRY YUSUFU WAKAWA; FASIHUDDIN BADRUDDIN AHMAD; SALE MUSA PUKUMA; HENRY BULAMA; JAMIMAH MOHAMMED MALGWI (Borneo Journal of Resource Science and Technology, 2022)
This work was designed to evaluate the antimicrobial potential of Morinda elliptica by determining the zone of growth inhibition of the leaf extract against selected bacterial and fungal strains. Antifungal and antibacterial properties of the extract at different concentrations (25, 50, 100, 250 and 500 μg/ml) were investigated after successive maceration in four solvents in order of increasing polarity [hexane (180 g), dichloromethane (342 g), ethyl acetate (471 g), and methanol (384)]. The agar disc diffusion method was used against selected human bacteria Escherichia coli, Salmonella typhii, Staphylococcus aureus, and the antifungal activity of the extract against Aspergillus brasiliences and A. flavus. Zones of growth inhibition of the extract were then compared with the standard antibiotic chloramphenicol (500 μg/ml) for the antibacterial activity, and against nystatin (500 μg/ml) for antifungal activity. The result of the study showed a remarkable bactericidal activity of the plant extract against the test organisms E. coli (14.667 + 0.577) and S. typhii (13.667 + 0.577) with a weak activity against the growth of S. aureus as compared to standard (21.667 + 0.577) at 500 μg/ml. The result of the antifungal activity showed considerable activity of the plant extract against the growth of A. brasiliences (11 + 0.1000) and weak activity against the growth A. flavus at 500 μg/ml. The findings of the study indicated that the leaf extract of M. elliptica is a reservoir of bioactive compounds. The compounds can be useful in the development of new pharmaceutical products that can be effective against human pathogenic strains E. coli and S. typhii. This could serve as a lead for understanding a novel mechanism of action in future research activities.